Perancangan Sistem Informasi Inventory Data Mapping Berbasis Web Di Pt. Trimitra Chitrahasta - Candra Naya; Danang Sutowo (Teknik Informatika, Universitas Pelita Bangsa, 2018)
Today's world continues to evolve through the era of the Industrial Revolution 3.0 where in this era various aspects have used computer technology and robots to help human activities, at this time the world began to embark on the Industrial Revolution 4.0 era where technological development became connected with the internet. But at PT.Trimitra Chitrahasta which is located in Delta Silicon 2 Industrial Estate Jl.Damar Blok F1-06 Lippo Cikarang Bekasi, is still experiencing difficulties in managing demand data and finding material placement locations. So there was an over-cost due to the length of time in the search for material that made the transport vehicle wait longer. The system that was developed based on needs will make it easier to use, with this system the process of finding material by the user will be easier by simply accessing it via a smartphone because the system is integrated with the internet. This system can speed up the process of finding material and can record all requests for goods so that each request can be held accountable for data that impacts on the regularity of data and data efficiency in the system